1992
DOI: 10.1038/ki.1992.130
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure in microalbuminuric type 1 diabetic patients

Abstract: Twenty-four-hour ambulatory blood pressure (AMBP) was performed in microalbuminuric (micro.) type 1 diabetic patients, with the aim of comparison with a matched group of normoalbuminuric patients (normo.) and healthy controls. Thirty-four patients without antihypertensive medication were investigated in each group. Urinary albumin excretion (UAE) for micro. was (geometric mean, tolerance factor microgram/min) 51.7 x/divided by 1.94, 5.1 x/divided by 1.88 for normo. and 5.2 x/divided by 1.75 for controls. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
4
5

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 40 publications
3
76
4
5
Order By: Relevance
“…Several studies have shown that non-dipping may be a marker, heralding development of microalbuminuria and diabetic nephropathy. [13][14][15][16][17][18] The proposed pathogenic is devoid of interruptions, and thus can be used as a model for tiled, non-interrupted sleep. We found that, both in diabetic patients and controls, blood pressure declined during the afternoon nap in a similar magnitude to the night-time decline.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that non-dipping may be a marker, heralding development of microalbuminuria and diabetic nephropathy. [13][14][15][16][17][18] The proposed pathogenic is devoid of interruptions, and thus can be used as a model for tiled, non-interrupted sleep. We found that, both in diabetic patients and controls, blood pressure declined during the afternoon nap in a similar magnitude to the night-time decline.…”
Section: Introductionmentioning
confidence: 99%
“…In all but one study no difference in BP was observed between healthy controls and patients with normoalbuminuric type 1 diabetes, when adjusting for albuminuria, diabetes duration, age and gender. 3,4,11,12,14,16,[25][26][27] We have used an automatic auscultatory device (Profilomat ® ) to measure 24-h BPs and found no significant difference in 'daytime' or 'night-time' BP or in systolic or diastolic day-night differences between diabetic patients and controls. These results are somewhat in contrast with data from studies in which 24-h BPs were measured with an oscillometric device.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although most cross-sectional as well as longitudinal studies on the prevalence of elevated BP in type 1 diabetes suggest an association between microalbuminuria and BP rise, it is still controversial whether the increase of arterial BP precedes, follows or develops in parallel with the onset of microalbuminuria. [2][3][4][5][6][13][14][15][16]23,24 These discrepancies on the prevalence of increased BP in type 1 diabetic patients at the onset of microalbuminuria can be attributed, at least partially, to differences in the study populations with respect to factors as age, diabetes duration, gender, sodiumintake, presence of autonomic neuropathy, the number of smokers vs non-smokers and urinary albumin excretion. However, from our data it is evident that differences in techniques of BP measurements should also be taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations